Given the wave equation:

$$ \frac{\partial^2 f}{\partial t^2} = c^2 \frac{\partial^2 f}{\partial x^2} $$

I change variables in this way:

$$ \xi = x+ct \\ \eta=x-ct $$

And the differential operators transform:

$$ \frac{\partial }{\partial x} = \frac{\partial }{\partial \xi} + \frac{\partial }{\partial \eta} \\ \frac{\partial }{\partial t} = c^2 ( \frac{\partial }{\partial \xi} - \frac{\partial }{\partial \eta} ) $$

I know this has something to do with the chain rule, but I'm not able to understand. How do I verify that these equalities are correct? How do I get to them?

Thank you.


Define $F(\xi,\eta)=f(t,x)$. Then, with some abuse of notation, $$ \frac{\partial}{\partial x}f(t,x)=\frac{\partial}{\partial x}F(\xi,\eta)=\frac{\partial F}{\partial \xi}\frac{\partial\xi}{\partial x}+\frac{\partial F}{\partial \eta}\frac{\partial\eta}{\partial x}=\frac{\partial F}{\partial \xi}+\frac{\partial F}{\partial \eta}. $$ This is the meaning of $$ \frac{\partial}{\partial x}=\frac{\partial }{\partial \xi}+\frac{\partial }{\partial \eta}. $$ A similar computation applies to the other derivative.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.